USING A MONOTONE SEQUENCE OF FUNCTIONS TO DETERMINE THE SHORTEST ARC LENGTH OF CIRCLES CONNECTED ANY TWO POINTS ON SPHERE - Muhammad Kabil Djafar; La Ode Safiuddin; Lilis Laome; Norma Muhtar; Herdi Budiman; Edi Cahyono; La. Gubu; Alfian Alfian; Indra Alamsyah; Askar Kohalsum (Barekeng, 2025)
This paper discusses about arc length of circles that connected any two points on a sphere. On a sphere, there are infinitely many circles that connect any two points. Using a monotone sequence of functions, we can show that the shortest arc length of circle that connect any two points on sphere is the circle with its center at the origin.